The Solution of a Two-dimensional Inverse Heat Transfer Problem Using the Trefftz Method. (2016) - Maciejewska, B.; Strąk, K.; Piasecka, M.
Abstract: This paper deals with a two-dimensional inverse heat transfer problem solved by means of the Trefftz method. The aim of the calculations was to determine the flow boiling heat transfer coefficient from the temperature measured by infrared thermography. The experiments concerning flow boiling heat transfer were conducted for two parallel asymmetrically heated rectangular minichannels. The element heating Fluorinert (FC-72) flowing in the minichannels was a thin foil, smooth on both sides in one channel and with enhanced surface on the side in contact with the fluid in the other channel. The enhanced surface was produced with iron powder deposited by soldering. The results are presented as infrared thermographs and plots of the heat transfer coefficient against the distance from the minichannel inlet. The values of the heat transfer coefficient were calculated using the Trefftz method. In the subcooled boiling region, the values of the heat transfer coefficient were relatively low, while in the saturated boiling region, they were very high. The local values of the heat transfer coefficient reported for the surface enhanced by soldering iron powder were only slightly higher.